Heroic Chancellor Winston Churchill and the University of Bristol, 1929 to 1965 - Cannadine, David (IHR Conference Series, 2017)
"Not only was Churchill the most illustrious and the most distinguished Chancellor that the University of Bristol has ever had, but he was also in his prime, from the 1940s onwards, probably the most famous and the most distinguished chancellor of any university anywhere in the world." David Cannadine